Construction Procurement Practice: A Review Study of Integrated Project Delivery (IPD) in the Malaysian Construction Projects - Nasrun Mohd Nawi; Sharifah Zaliha Syed Zuber; Faizatul Akmal Abdul Nifa (International Journal of Supply Chain Management, 2019)
Integrated Project Delivery (IPD) is a project method like none other since it emerged as a method that emphasizes on the integration of all aspects involved in the construction project. This paper is theory based and the objectives are to explore the concept of IPD by synthesizing the existing definitions, describing its principles, comparing its delivery phase with other primary project delivery methods, namely Design-Bid-Build (DBB), Construction Manager at Risk (CM at Risk), and Design-Build (DB), and describing the challenges of its implementation under several issues, such as organizational, financial, legal, and technological aspects. Even though in principle, carrying out IPD is able to bring success to a construction project, its implementation in the construction industry is challenging. Therefore, this study has suggested that the development of new ideal project delivery methods is a necessity in order to overcome the existing issues in project delivery methods, toward achieving project success.